Estudo descritivo sobre os pacientes atendidos no ambulatório de neurologia do Hospital de Clínicas Gaspar Vianna, no período de março de 2004 a março de 2007 - CARVALHAL, Cyro Daniel (2022)
This study provides scope to describe the clinical epidemiological profile of elderly population in the Clinic of Neurology, Clinic Hospital Gaspar Vianna (HCGV), emphasizing the cognitive findings, as a health reference institution in the North in the area of psychiatry and to develop a important work with people of Alzheimer's. Thus was developed a theory-based, with emphasis on the demographic aspects of aging; elucidating aspects about the elderly and the ill, physiology and anatomy of the central and peripheral nervous system, human memory, morphological changes in the elderly and dementia, and how scope of the study, the Alzheimer's and their drug treatments and non-medicated. This is because, from a qualitative, bringing also support various authors that explore the theme worked. The data analysis undertaken here has thematic discussions, obtained from the survey of records related to the implementation of the research protocol of patients enrolled from March 2004 to March 2007. The draft of this research was approved by the Ethics Committee of the hospital. The average population served showed: evolution unchanged (55%), female (62%), school average (27.5%) and time of complaint > 1 year (63%). The results indicated the need for an extension of the concept of dementia not to continue the difficulties of diagnosis, particularly in the initial phase of the process when, often, the patient is unrelated to their cognitive deficits or try to minimize them and disguising them, not to mention the important recognition of the family in care and the need for inter-and multidisciplinary work, to an adequate preparation of professionals, to enhance the human aspects of care to elderly patients.